Decision making under the environmental perspective: Choosing between traditional and distance teaching courses. (20th January 2018) - Oliveira, J.H.; Giannetti, B.F.; Agostinho, F.; Almeida, C.M.V.B.
Abstract: Over the last 30 years, distance learning has rapidly spread in developed countries, and to niche markets in developing countries. In Brazil, approximately 5 million people are currently either achieving formal education or corporate training, or obtaining specific knowledge and skills on a wide range of subjects, via distance learning. Motivated by the ongoing expansion of the Brazilian federal chain of public schools, several new campuses, extra classrooms and distance teaching centers have been built, as a function of the intensive promotion of social inclusion by means of education, and specifically allocated budget. Concomitantly, a considerable number of papers discussing reduction of energy and materials consumption in university campuses have been published. Intended as a contribution to this discussion, this work evolves from a comparison of the implicit environmental cost – i.e. the use of natural resources as the prime-matter of infrastructural and operational material, and source of energy to human work-in forming management technicians in a classroom course, and in a distance learning course, obtained from the results of two case studies carried out at a Federal Institute campus in Brazil. The groups were selected for their relative closeness in proportion of attending students. Data were collected by means of measurements and interviews, and a synthesis of the use of natural resources by both modes was obtained by using the emergy accounting method, and then compared. The emergy method was also used to assess current use and underuse rates of the available infra-structural resources. Scenarios based on different numbers of students and teaching staff attending capacity for both modes, distance learning and classroom, were created and compared. Results point out that, under the current configurations, forming a management technician via distance teaching requires a 90% higher environmental support than via classroom teaching. The scenarios, however, do indicate a turning point. Highlights: Distance teaching requires a 90% higher environmental support than via classroom teaching. Insights for reducing resource use on educational buildings are provided. The environmental costs of the move towards distance teaching are evaluated. A viable procedure to assess and monitor the greening of campuses' facilities is established. The procedure enables for the assessment/comparison/selection of course-modality-to-be-adopted.